The changing careers of patients with chronic mental illness: A study of sequential patterns in mental health service utilization - Wuerker, Anne K. (Journal of mental health administration, 1996)
The aim of this study was to describe patterns of service use over time by a group of persons with chronic mental illness who were homeless at the time of the index admission. Subjects were all persons admitted to Skid Row Mental Health Services in a recent year who had 25 or more previous admissions to any Los Angeles County Department of Mental Health service (N = 49). Sequences of type of service at each of the 25 admissions were compared with optimal matching and categorized with cluster analysis. Patients in earlier clusters had many inpatient admissions; those in later clusters had many admissions to outpatient, residential, and jail services. Service use by individuals in each cluster showed the same trends. However, there were also different patterns of service use for patients in cluster within the same tie frame. Analyzing multiple admissions sequentially helps to locate likely places to intervene in downward-spiraling careers.